URGENSI PENYELENGGARAAN PENDIDIKAN ANTI KORUPSI PADA SETIAP JENJANG PENDIDIKAN BERDASARKAN UU NOMOR 30 TAHUN 2002 - Vivi Sandra (Program Studi PPKn Universitas Pendidikan Ganesha, 2022)
Anti-corruption education is a process of introducing and teaching knowledge about corruption through formal education to create anti-corruption attitudes and habits. It is known that the reason for holding anti-corruption education is because of the increasingly widespread cases of corruption that have occurred in Indonesia and have targeted many groups, both public officials and students. Therefore, it is important to organize anti-corruption education, especially at every level of education. The aim is to form an anti-corruption character as possible among students as an effort to prevent corruption. Based on the explanation of the issues discussed, the results of this research can be presented, namely: First, anti-corruption education is important to be held as an effort to prevent corruption. Second, organizers of anti-corruption education can be held at any elaboration of education according to the provisions of Law no. 30 of 2002. Third, anti-corruption education providers are considered to be more effective in building awareness and an anti-licensing culture towards corruption.